Coronavirus virus disease (COVID-19) outbreak Americas [electronic resource] - World Health Organization. Regional Office for the Americas (Washington, D.C. Pan American Health Organization, 2020)
COVID-19 is an emerging, rapidly evolving situation. Get the latest public health information from this site.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Open education; Open access publishing; Education, Higher; COVID-19 (Disease) -- Research -- Electronic information resources; COVID-19 (Disease) -- America -- Electronic information resources; Open access publishing; Anguilla -- COVID-19 (Disease) -- Electronic information resources; Antigua and Barbuda -- COVID-19 (Disease) -- Electronic information resources; Argentina -- COVID-19 (Disease) -- Electronic information resources; Aruba -- COVID-19 (Disease) -- Electronic information resources; Bahamas -- COVID-19 (Disease) -- Electronic information resources; Barbados and the Eastern Caribbean Countries -- COVID-19 (Disease) -- Electronic information resources; Belize -- COVID-19 (Disease) -- Electronic information resources; Bermudal -- COVID-19 (Disease) -- Electronic information resources; BIREME -- COVID-19 (Disease) -- Electronic information resources; Bolivia -- COVID-19 (Disease) -- Electronic information resources; Brazil -- COVID-19 (Disease) -- Electronic information resources; British Virgin Islands -- COVID-19 (Disease) -- Electronic information resources; Canada -- COVID-19 (Disease) -- Electronic information resources; Caribbean Subregional Program Coordination -- COVID-19 (Disease) -- Electronic information resources; Cayman Islands -- COVID-19 (Disease) -- Electronic information resources; Childe -- COVID-19 (Disease) -- Electronic information resources; Colombia -- COVID-19 (Disease) -- Electronic information resources; Costa Rica -- COVID-19 (Disease) -- Electronic information resources; Cuba -- COVID-19 (Disease) -- Electronic information resources; Curacao -- COVID-19 (Disease) -- Electronic information resources; Dominica -- COVID-19 (Disease) -- Electronic information resources; Dominican Republic -- COVID-19 (Disease) -- Electronic information resources; Ecuador -- COVID-19 (Disease) -- Electronic information resources; El Salvador -- COVID-19 (Disease) -- Electronic information resources; French Guiana -- COVID-19 (Disease) -- Electronic information resources; Grenada -- COVID-19 (Disease) -- Electronic information resources; Guadeloupe -- COVID-19 (Disease) -- Electronic information resources; Guatemala -- COVID-19 (Disease) -- Electronic information resources; Guyana -- COVID-19 (Disease) -- Electronic information resources; Haiti -- COVID-19 (Disease) -- Electronic information resources; Honduras -- COVID-19 (Disease) -- Electronic information resources; Jamaica -- COVID-19 (Disease) -- Electronic information resources; Latin American Center of Perinatology, Women and Reproductive Health (CLAP/WR) -- COVID-19 (Disease) -- Electronic information resources; Martinique -- COVID-19 (Disease) -- Electronic information resources; Mexico -- COVID-19 (Disease) -- Electronic information resources; Montserrat -- COVID-19 (Disease) -- Electronic information resources; Netherlands Antilles -- COVID-19 (Disease) -- Electronic information resources; Nicaragua -- COVID-19 (Disease) -- Electronic information resources; Pan American Foot-and-Mouth Disease and Veterinary Public Health Center - PANAFTOSA -- COVID-19 (Disease) -- Electronic information resources; Panama -- COVID-19 (Disease) -- Electronic information resources; Paraguay -- COVID-19 (Disease) -- Electronic information resources; Peru -- COVID-19 (Disease) -- Electronic information resources; Puerto Rico -- COVID-19 (Disease) -- Electronic information resources; Saint Kitts and Nevis -- COVID-19 (Disease) -- Electronic information resources; Saint Lucia -- COVID-19 (Disease) -- Electronic information resources; Saint Vincent and the Grenadines -- COVID-19 (Disease) -- Electronic information resources; Sint Maarten -- COVID-19 (Disease) -- Electronic information resources; Subregional Program for South America -- COVID-19 (Disease) -- Electronic information resources; Suriname -- COVID-19 (Disease) -- Electronic information resources; Trinidad and Tobago -- COVID-19 (Disease) -- Electronic information resources